Efficacy and safety of Lianhua Qingwen granule combined with azithromycin for mycoplasma pneumoniae pneumonia in children: a systematic review with meta-analysis and trial sequential analysis - Li, Jiawei; Ma, Yuqi; Qi, Jiawen; Hao, Yule; Wang, Yiming; Wu, Yeke (Frontiers in Pharmacology, 2024)
Lianhua Qingwen (LHWQ) granule, a botanical drug preparation, is frequently utilized as an adjuvant treatment for mycoplasma pneumoniae pneumonia (MPP). Nevertheless, the clinical efficacy and safety of this treatment remain uncertain. This study aims to evaluate the efficacy and safety of LHWQ granule combined with azithromycin (AZM) in treating MPP in children. A search was conducted in eight Chinese and English databases from their inception until December 25, 2023. Meta-regression and subgroup analysis were employed to investigate heterogeneity. Sensitivity analysis and trial sequential analysis (TSA) were conducted to assess the robustness of the findings. Additionally,GRADE system was utilized to evaluate the quality of evidence. A total of 15 RCTs involving 1909 participants were included. The meta-analysis results indicated combination therapy of LHQW granule and AZM is significant different from AZM alone in both efficacy and safety, which are specifically observed in the following outcomes: response rate (RR = 1.17, 95 % CI: 1.12 to 1.22, P＜0.01), antipyretic time (MD = -1.32, 95% CI: -1.66 to -0.98, P＜0.01), cough disappearance time (MD = -1.76, 95% CI: -2.47 to -1.05, P＜0.01), pulmonary rale disappearance time (MD = -1.54, 95% CI: -2.06 to -1.02, P＜0.01), c-reactive protein (CRP) (MD = -5.50, 95% CI: -6.92 to -4.07, P＜0.01), procalcitonin (PCT) (MD = -0.31, 95% CI: -0.38 to -0.24, P＜0.01), interleukin 6 (IL-6) (MD = -5.97, 95% CI: -7.39 to -4.54, P＜0.01), tumor necrosis factor α (TNF‐α) (MD = ‐5.74, 95% CI: ‐7.44 to ‐4.04, P＜0.01), forced vital capacity (FVC) (SMD = 0.48, 95% CI: 0.34 to 0.62, P＜0.01), forced expiratory volume in the first second (FEV1) (SMD = 0.55, 95% CI: 0.44 to 0.67, P＜0.01), FEV1/FVC (SMD = 0.49, 95% CI: 0.32 to 0.67, P＜0.01), CD4+ T lymphocyte (CD4+) (MD = 4.04, 95% CI: 3.09 to 4.98, P＜0.01), CD8+ T lymphocyte (CD8+) (MD = -3.32, 95% CI: 4.27 to 2.38, P＜0.01) and adverse events (RR = 0.65, 95% CI: 0.43 to 0.96, P＜0.01). The combination therapy of LHQW granule and AZM may be a better strategy to treat MPP in children. However, clinical efficacy and safety of LHQW granule require further validation.